Neogene Mass Accumulation Rate of Carbonate Sediment Across Northern Zealandia, Tasman Sea, Southwest Pacific. Issue 2 (11th February 2022) - Sutherland, R.; Dos Santos, Z.; Agnini, C.; Alegret, L.; Lam, A. R.; Westerhold, T.; Drake, M. K.; Harper, D. T.; Dallanave, E.; Newsam, C.; Cramwinckel, M. J.; Dickens, G. R.; et al.
Abstract: Sediment mass accumulation rate (MAR) is a proxy for paleoceanographic conditions, especially if biological productivity generated most of the sediment. We determine MAR records from pelagic calcareous sediments in Tasman Sea based on analysis of 11 boreholes and >3 million seismic reflection horizon picks. Seismic data from regions of 10, 000–30, 000 km 2 around each borehole were analyzed using data from International Ocean Discovery Program Expedition 371 and other boreholes. Local MAR was affected by deepwater currents that winnowed, eroded, or deposited seafloor sediment. Therefore, it is necessary to average MARs across regions to test paleoceanographic and productivity models. MARs during the Miocene Climate optimum (18–14 Ma) were slightly lower than Quaternary values but increased on southern Lord Howe Rise at 14–13 Ma, when global climate became colder. Intensification of the Indian and East Asian monsoons at ∼8 Ma and ∼3.6 Ma approximately corresponds to the start and end, respectively, of the Biogenic Bloom, which had MARs at least double Quaternary values. On northern Lord Howe Rise, we recognize peak MARs at∼7 Ma and ∼5 Ma. There is no correlation between Neogene MAR and ocean pH or atmospheric CO2 concentration. Neogene MARs are on average higher than Quaternary values. We posit that future long‐term productivity in the southwest Pacific could be higher than Quaternary values, but new computer models that can fit our observations are required to test this hypothesis. Plain Language Summary: Global climate is likely to get warmer, and we want to know what will happen to marine life. We can study ancient warm periods to better predict the future. The ocean is a global carbon sink, because some organisms form shells by combining calcium with carbon dioxide dissolved in seawater. Once dead, their calcium carbonate shells sink to the seabed. Over millions of years, the southwest Pacific accumulated huge deposits. We used geophysical surveying and drilling to measure this history of deposition, which is a proxy for ancient biological productivity (how much marine life existed). A warm period 18–14 million years ago had high atmospheric carbon dioxide (2–4 times preindustrial levels) and slightly lower ocean productivity. In contrast, 8–4 million years ago, atmospheric carbon dioxide was similar to predicted 21st century levels and productivity was much higher: more than double recent values. Rates of calcium carbonate deposition in the past do not correlate with ocean acidity or atmospheric carbon dioxide; but they were mostly higher than today. Hence, long‐term biological productivity and carbon sequestration in the southwest Pacific might increase in future, but computer models that fit our observations are needed to test this idea. Key Points: Marine carbonate productivity in Tasman Sea varied by a factor of 3–5 since 25 Ma Peak Neogene productivity was at 7–5 Ma and was more than double that since 2 Ma Currents and gravity flows resulted in high spatial variability of mass accumulation rate